Would you like some fries with your ecosystem services?: McDonaldization and conservation in Prince Edward Island, Canada. Issue 111 (May 2020) - Kolinjivadi, Vijay; Bissonnette, Jean-François; Zaga Mendez, Alejandra; Dupras, Jérôme
Highlights: McDonaldization reflects efficiency, predictability, calculability, and control. We explore the consequences of justifying conservation through McDonaldization. Payments for Ecosystem Services risk optimizing conservation to enhance production. We explore how PES expands frontiers of intensive production on Prince Edward Island. Solutions may lie in social and ecological "irrationalities" of production logics. Abstract: In response to widespread soil erosion, biodiversity loss, and rapid social and ecological homogenization of agri-environmental landscapes, economic incentives such as payments for ecosystem services (PES) are presented by natural resource managers as the most efficient way to address the unintended consequences of intensive agriculture. In this article, we explore the consequences of rationalizing conservation by adopting sociologist George Ritzer's "McDonaldization" thesis to contextualize on-farm conservation payments to farmers on Prince Edward Island (PEI), Canada. McDonaldization refers to the rendering of both society and nature in increasingly calculable, predictable, efficient and controllable ways. Through the introduction of economic incentives for conservation in the context of increasing pressures to maximise yields of processed potatoes in PEI, we discuss how debates on designing conservation payments are framed in terms of optimizing efficiency and maintaining predictability. In some cases, conservation is viewed as generating new productive values from agricultural landscapes, including for values of "care" "community" and "resilience, " that can be commodified for profit. We emphasize how intensifying agriculture necessitates economically beneficial conservation practices to both pre-empt future production losses and to reproduce the conditions necessary for optimizing future production. Within this arrangement of disciplining unexpected outcomes with ever-uniform, predictable, and controllable responses, we conclude that dynamic spontaneity of unexpected social and ecological responses and the politicization of farmer autonomy may avoid the tendency towards reinforcing business-as-usual agricultural production.